Microwave casting of stainless still through microwave hybrid heating. Issue 1 (1st July 2022) - Ram, Vishal Kumar; Nandwani, Sahil; Vardhan, Sachit; Bahl, Shashi; Samyal, Rahul; Bagha, Ashok Kumar
Abstract: A microwave is defined as a form of electromagnetic radiation. The microwave has an electric-field and magnetic field and those fields are orthogonal to each other and within the frequency range of 0.3-300 GHz. Microwave casting is a novel technique to cast different materials using microwave hybrid heating (MHH). The microwave casting is divided into two parts, such as in-situ and ex-situ. In this paper, the in-situ microwave casting process is used to cast the SS316bulk metal. A domestic microwave applicator has a frequency of 2.45 GHz with a power capacity of 900W. Stainless steel was used as a powder form having a particle size of 40-80 μm. SEM, EDS, and micro-hardness of the casted samples are carried out to validate the casting of SS316 bulk metal. The modal analysis of casted beam using experimental OROS software technique to measure the natural frequencies, corresponding damping ratios, and damping capacity of the casted SS316 samples.